Utilization of Ecoenzyme Citrus reticulata in a microbial fuel cell as a new potential of renewable energy - Imelia Dewi; Laksmi Ambarsari; Akhiruddin Maddu (Jurnal Kimia Sains dan Aplikasi, 2020)
The world's energy needs generally come from non-renewable sources. In other circumstances, some research on renewable energy is being developed from a variety of different sources, one of which is biomass. Biomass changes the energy system towards the modernization of the bioenergy system by utilizing the concept of biochemical systems (BESs). A microbial fuel cell is known as one of the renewable technologies that convert biomass with the help of microbes to produce electricity. This research is based on a microbial fuel cell based on ecoenzyme Citrus reticulata known as Ecoenzyme fuel cell to determine the electrical value (voltage, current, and power density). Ecoenzyme was made from orange peel waste, molasses, and water with a ratio of 3: 1: 10 and fermented for a month. Meanwhile, the electrode device used was a pencil graphite. Some treatments were carried out to optimize the performance of the system based on the number of electrodes (one pair and three pairs), and the stirring conditions, stirring at 200 rpm and without stirring (0 rpm). The EFC system was run for four weeks (600 hours) with the highest voltage obtained at 650 mV and current at 29.55 mA. The ecoenzyme produced the most significant power density of 750 W/m2 in the treatment of 3 electrode pairs with a stirring speed of 200 rpm. The influence of electrodes and stirring in the MFC system upsurged the electrical value output by 53.7% for a pair of electrodes and 142% for three electrode pairs. Further development will continue to be done to improve the performance and output of the Ecoenzyme fuel cell system as a future renewable energy source in Indonesia.